The Volatilomes of Symbiodiniaceae-Associated Bacteria Are Influenced by Chemicals Derived From Their Algal Partner - Lawson, Caitlin A.; Seymour, Justin R.; Possell, Malcolm; Suggett, David J.; Raina, Jean-Baptiste (Frontiers in Marine Science, 2020)
Biogenic volatile organic compounds (BVOCs) are a large group of molecules involved in trophic interactions, stress response and atmospheric chemistry. Although they have been extensively studied in terrestrial ecosystems, their identity and prevalence in the marine environment remains largely unexplored. Here we characterised the volatilome of two abundant marine bacteria that were previously identified as members of the core microbiome of Symbiodiniaceae (phylum: Dinoflagellata), the photosynthetic endosymbionts of reef building corals. To determine the influence of Symbiodiniaceae exudate on their associated bacteria, we incubated isolates of Marinobacter adhaerens HP15 and Labrenzia sp. 21p with Symbiodiniaceae culture filtrate or culture medium (control) and investigated their volatilomes using GC-MS. The volatilome of Labrenzia sp. incubated in Symbiodiniaceae filtrate was significantly different and more diverse relative to the control. In contrast, the overall composition of the M. adhaerens volatilomes were consistent between treatment and control. Among the 35 compounds detected in both bacterial species, the dominant chemical functional groups were halogenated hydrocarbons, aromatic hydrocarbons and organosulfurs, some of which are known to play roles in inter-organism signalling, to act as antioxidants and as antimicrobials. This study provides new insights into the potential sources and diversity of marine BVOCs, uncovering a wide range of molecules that may play important physiological and ecological roles for these organisms, while also revealing the role of Symbiodiniaceae-associated bacteria in the emission of important atmospheric gases.